Physical Quality of Complete Pellets Feed Containing Peanut Waste (Arachis hypogaea) and Its Effects on Rabbit Growth Performance - Riski Amelia Jaini; Yuli Retnani; Didid Diapari (Buletin Peternakan, 2023)
This study aimed to evaluate the physical quality of complete pellets with the addition of peanut waste and the effect of its administration on the performance of rabbits. A total of 20 local male rabbits aged 12 weeks with an average body weight of 1335.60 ± 280.53 g are divided into five groups based on body weight, and then used in this study which is performed in randomized block design (RBD). The rabbits are fed on the commercial pellets as a control diet (P0) and feed pellets containing peanut waste at the level of 5% (P1), peanut waste 10% (P2), and peanut waste 15% (P3). The results show that the physical quality of the pellets was not significantly different (p>0.05) in all treatments. Feeding complete pellets with the addition of peanut waste rabbits performances show no significant difference in performance (p>0.05) in all treatments. In conclusion, complete pellets with the addition of peanut was can resemble the physical quality of commercial pellets (control), maintain performances